Novel noninvasive biomarkers of prodromal Alzheimer disease: The role of optical coherence tomography and optical coherence tomography-angiography - Biscetti, Leonardo; Lupidi, Marco; Luchetti, Elisa; Eusebi, Paolo; Gujar, Ramkailash; Vergaro, Andrea; Cagini, Carlo; Parnetti, Lucilla (European journal of neurology, 2021)
BACKGROUND AND PURPOSE: A reduction of retinal thickness and an alteration of retinal perfusion have been found in Alzheimer disease (AD). Nowadays, retinal layers and retinal perfusion can be evaluated by means of noninvasive imaging techniques, namely, optical coherence tomography (OCT) and OCT-angiography (OCT-A). Here, we have compared the retinal thickness and the perfusion index, measured by means of OCT and OCT-A, in patients with mild cognitive impairment due to AD (MCI-AD) and in age- and sex-matched cognitively healthy controls. METHODS: Twenty-four MCI-AD patients and 13 control subjects were enrolled. MCI-AD patients underwent lumbar puncture; all of them showed a cerebrospinal fluid (CSF) profile compatible with AD. OCT was used for evaluating retinal volumes and thicknesses, whereas with OCT-A we measured fractal dimension (FD), vascular perfusion density (VPD), and vessel length density (VLD) of superficial capillary plexus (SCP), intermediate capillary plexus (ICP), deep capillary plexus (DCP), and choriocapillaris. The comparisons between groups were made after adjustment for age, diabetes, and hypertension. RESULTS: A significant reduction of SCP-VLD (p = 0.012), ICP-VPD (p = 0.015), ICP-VLD (p = 0.004), DCP-VPD (p = 0.012), and DCP-VLD (p = 0.009) was found in MCI-AD patients compared to controls. Conversely, FD was higher in MCI-AD than in controls (p = 0.044). CSF Aβ42/total tau negatively correlated with FD (r = -0.51, p = 0.010). CONCLUSIONS: OCT-A might have a potential role in detecting new noninvasive biomarkers for early AD detection. Retinal VPD might identify amyloid angiopathy-related chronic injury, and FD could show early vessel recruitment as a compensative mechanism at disease onset. Further studies will be needed to confirm these findings.
Keywords: optical coherence tomography; Retinal Vessels; Alzheimerova nemoc; mild cognitive impairment; optická koherentní tomografie; OCT-angiography; lidé; Tomography, Optical Coherence; biologické markery; diagnostic biomarkers; fluoresceinová angiografie; OCT; Biomarkers; Alzheimer Disease; Alzheimer disease; retinální cévy; Fluorescein Angiography; Humans